Relationship Between Demographic Variables and Job Outcomes of Clinical Nurses in NABH Accredited Hospitals - P, Ashwini; Indradevi, Dr R. (The journal of contemporary issues in business and government, 2023)
One of the most important and much-needed services in patient care is nursing. Managing an employee in the hospital industry is difficult, and addressing their requirements is critical. Nurses are crucial in ensuring that the requirements of patients are satisfied. Nurses and the organization's goals both benefit from increased job satisfaction. In this study, clinical nurses working in NABH-accredited hospitals in Tamil Nadu are examined to see how demographic factors such as age, years of service, and designation affect outcomes such as job satisfaction, involvement in the workplace, organisational commitment (attitude), job stress (psychological), and turnover intention (behavioural).